2018
DOI: 10.1101/427609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural brain alterations in youth with psychosis and bipolar spectrum symptoms

Abstract: Objective: Adults with established diagnoses of serious mental illness (bipolar disorder and schizophrenia) exhibit structural brain abnormalities, yet less is known about how such abnormalities manifest earlier in development. Methods:We analyzed the data publicly available from the Philadelphia Neurodevelopmental Cohort (PNC).Structural magnetic resonance neuroimaging data (sMRI) were collected on a subset of the PNC (N=989, ages 9-22 years old). We calculated measures of cortical thickness (CT) and surface … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
2
1
0
Order By: Relevance
“…Comparative studies in adult patients have pointed to specificity of surface area reduction for schizophrenia (Rimol et al, 2012), while a recent meta‐analysis has suggested that surface area decrease in bipolar disorder may only be present in patients with psychotic symptoms (Hibar et al, 2018), which coincides with our observations. Our findings also concur with recent data from a community‐based study in adolescents which also described cross‐sectional frontal and parietal surface area reduction in youth showing psychotic – but not bipolar – spectrum symptoms (Jalbrzikowski et al, 2019), which mirrors the lack of effect of mood diagnoses on our findings at cross‐section. Only follow‐up of the current sample into adulthood will resolve questions concerning prediction of specific diagnostic outcomes in these youth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparative studies in adult patients have pointed to specificity of surface area reduction for schizophrenia (Rimol et al, 2012), while a recent meta‐analysis has suggested that surface area decrease in bipolar disorder may only be present in patients with psychotic symptoms (Hibar et al, 2018), which coincides with our observations. Our findings also concur with recent data from a community‐based study in adolescents which also described cross‐sectional frontal and parietal surface area reduction in youth showing psychotic – but not bipolar – spectrum symptoms (Jalbrzikowski et al, 2019), which mirrors the lack of effect of mood diagnoses on our findings at cross‐section. Only follow‐up of the current sample into adulthood will resolve questions concerning prediction of specific diagnostic outcomes in these youth.…”
Section: Discussionsupporting
confidence: 93%
“…The field has only recently begun to look towards childhood and adolescence as a critical period for understanding development of major adult mental health outcomes. Studies in adolescents at varying degrees of risk for psychosis, identified either following an 'ultrahigh risk' approach (Cannon et al, 2015) or through community-based samples (Jalbrzikowski et al, 2019), have associated psychotic spectrum symptoms with global and regional grey matter volume and cortical thickness reductions. However, all above studies have relied on either cross-sectional designs or limited follow-up periods, which curtails the ability to capture differences in trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by (1) normalization of cortical surface area when transitioning into adulthood; (2) cortical surface area alterations being only present in a specific subgroup (subtype) of adult patients with adolescent-onset MDD, which we were unable to detect; or (3) those with cortical surface area alterations in early adolescence may be at higher risk for transitioning from MDD to other mental disorders over time. This latter possibility is consistent with reports of lower cortical surface area in adolescents and adults with psychosis or schizophrenia 82,83 , and in individuals at high risk for and/or transitioning to psychosis 84,85 . Longitudinal studies are required to test the hypothesis that cortical surface area alteration is a pre-existing risk factor for the development of MDD, and to investigate the subsequent clinical course of these young people with MDD and global surface area reductions.…”
Section: Subcortical Brain Regionssupporting
confidence: 91%